If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-123=5x+6(x-4)
We move all terms to the left:
-123-(5x+6(x-4))=0
We calculate terms in parentheses: -(5x+6(x-4)), so:We get rid of parentheses
5x+6(x-4)
We multiply parentheses
5x+6x-24
We add all the numbers together, and all the variables
11x-24
Back to the equation:
-(11x-24)
-11x+24-123=0
We add all the numbers together, and all the variables
-11x-99=0
We move all terms containing x to the left, all other terms to the right
-11x=99
x=99/-11
x=-9
| 22+r=32 | | 5x-13=19-8x | | 1.75(3+b)=9.25 | | 5(b+1)+6(6b+3)=23 | | (3m-5)2+7(3m-5)+12=0 | | 9j−8=8+9j | | 5=11n=13n | | 16n+3+4n=103 | | 4(b+5)−9=−7 | | x=0.1+.5 | | 4(x-28)=0.3(x+2)2.11 | | -3(3y-10)-y=-4(y-2) | | -4(5+7v)=7v+15 | | -13-(-14)=x/7 | | -2(2x+3)=-4(x+1)+2 | | 9x4xx=360 | | 12=3/2a-12 | | -1=9=p/8 | | -6x+4(-5x+16)=-92 | | 3x÷20=15;x÷=2 | | 150x+25x=55x | | 5(3c-1)-5=12c+8 | | -6u=-7u-7 | | -6x-9x-14=-2x+2 | | 6x-1-7x=x+5+x | | f=2(-3)^2-3(-3)+1 | | 7x-9=x-45 | | 14y=2(y+5)-2 | | 1/3y−5=1/9y | | 8m^2+14m-9=0 | | 1/3y−5=1/9y. | | 5(3+x)=3(x+3)-4x |